2020
DOI: 10.1111/ggi.13928
|View full text |Cite
|
Sign up to set email alerts
|

Biology of extracellular vesicles secreted from senescent cells as senescence‐associated secretory phenotype factors

Abstract: The increase of the morbidity rate in age‐related diseases, such as cancer, Alzheimer’s disease, arteriosclerosis and pulmonary fibrosis, has become a profound social problem. Recent reports have pointed out that senescent cells accumulated in the body with aging might cause these aged‐related pathologies. Cellular senescence is known as an irreversible cell cycle arrest induced by various stresses, and can function as an important tumor suppression mechanism to exclude the premalignant cells. In contrast, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 94 publications
(166 reference statements)
0
33
0
Order By: Relevance
“…The expression of five gene transcripts ( Cdkn2a , Apobec3 , Magi2 , Parp3 , and Cass4 ) significantly increased with age, and their expression in the blood was correlated to that in the hippocampus only in AD mice (Table 3 ). CDKN2A is a well-known molecular player in cellular senescence, cell proliferation, survival, adhesion, and apoptosis [ 23 , 24 ]. An increased level of Cdkn2a is present in both brain and blood cells from APP/PS1 mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of five gene transcripts ( Cdkn2a , Apobec3 , Magi2 , Parp3 , and Cass4 ) significantly increased with age, and their expression in the blood was correlated to that in the hippocampus only in AD mice (Table 3 ). CDKN2A is a well-known molecular player in cellular senescence, cell proliferation, survival, adhesion, and apoptosis [ 23 , 24 ]. An increased level of Cdkn2a is present in both brain and blood cells from APP/PS1 mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To verify the reliability of the microarray data, we selected Cdkn2a for qPCR experiments because this gene exhibited the greatest changes among the five candidate genes and is well known as an aging-and cellular senescence-associated gene [23,24]. This analysis aimed to not only validate the correlations between the microarray and real-time PCR data but also confirm the detection of well-known changes.…”
Section: Real-time Pcr Validation Of Degs In Microarray Datamentioning
confidence: 99%
“…This process collectively refers to as senescence-associate secretory phenotype (SASP) ( Li et al, 2018 ). The molecules secreted from SASP can also be packed in EV format ( Misawa et al, 2020 ). This persistent insult from SASP leads to the delayed effect of irradiation-induced senescence, such as fibrosis in the lung ( Citrin et al, 2013 ; He et al, 2019 ), oral mucositis ( Iglesias-Bartolome et al, 2012 ), cardiovascular disease ( Stewart et al, 2013 ), hypo-salivation ( Peng et al, 2020 ), hematopoietic cell senescence ( Wang et al, 2011 ).…”
Section: Evs For Radiation MCMmentioning
confidence: 99%
“…In another study, downregulation of antioxidant enzyme genes and cellular redox system (iNOS2) genes was observed in non-irradiated mice as a bystander effect when injected with bone marrow-EVs from irradiated mice ( Hargitai et al, 2021 ). In the same token, recent evidence suggests that EVs as SASP, secreted from senescent cells might contribute to tumorigenesis and age-associated pathologies ( Misawa et al, 2020 ). It can be a potential mechanism to explain a high incidence of cancer developed in the survivors after radiation exposure.…”
Section: Evs For Radiation MCMmentioning
confidence: 99%
“…SASP has been regarded as a critical factor in the occurrence and development of age-related diseases 7 . Some studies have indicated that senescent cells secrete not only inflammatory cytokines, chemokines, and matrix metalloproteinases but also exosomes 8 . Exosomes are double-layered membrane vesicles secreted by cells and play a crucial role in the material exchange and information transduction between cells 9 .…”
Section: Introductionmentioning
confidence: 99%